Der österreichische Neoabsolutismus als Verfassungs- und Verwaltugsproblem Diskussionen über einen strittigen Epochenbegriff - Brandt, Harm-Hinrich (2014)
This volume includes the elaborated papers and discussions of a conference held at Würzburg on Austrian ,Neoabsolutism' (1849/51-1860/61). Starting point was the recent criticism of that term to identify the Austrian type of postrevolutionary government and to mark a historical period. The experts assembled at Würzburg focussed their analysis on the various fields of domestic policy in that ambiguous decade and tried to evaluate its importance within the long-term problems of the Hapsburg Monarchy.